A modified high output-gain cuk converter circuit configuration for renewable applications - A comprehensive investigation - Oluwafemi A.W.; Ozsoy E.; Padmanaban S.; Bhaskar M.S.; Ramachandaramurthy V.K.; Fedk V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Energy conversion; HVDC power transmission; MATLAB; Timing circuits; Analytical analysis; BOOST converter; Circuit components; DC-DC boost converters; High gain; High-voltage converter; Photovoltaic; Renewable energy applications; DC-DC converters